All that makes life bright [large type] : the life and love of Harriet Beecher Stowe - Kilpack, Josi S. (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Harriet Beecher marries Calvin Stowe in 1836, sure of a future filled with romance, a family, and her writing. Calvin is supportive, and Harriet is determined to preserve her independent spirit. Two months later, she discovers she's pregnant just as Calvin leaves for a European business trip. Overwhelmed, Harriet feels like she's living another woman's life. Struggling to balance being a wife and mother with her passion for writing and social change, Harriet works to build a life with her beloved Calvin.